Who Wrote This?: Modern Forensic Authorship Analysis as a Model for Valid Forensic Science - Janet Ainsworth; Patrick Juola (Washington University Law Review, 2019)
The forensic analysis of a text in order to determine its authorship has, for decades, been accomplished by forensic linguists. These experts are trained in the science of linguistics, and have often applied their specialized expertise in sociolinguistics, discourse analysis, and pragmatics. Although the range of applications for forensic linguistics is extremely wide, this Article will focus only on the authorship attribution application. Herein, we maintain that reliability is an essential component of pattern comparison forensic practices, that testing for validity and measuring of error rates are the Daubert factors that best guarantee reliability, and that the practices of authorship attribution can be an effective model of how to carry out this testing.
Keywords: Forensic science; Authorship analysis; Forensic linguists; Authorship attribution; Evidence; Forensic stylometry